The Forging of a “Singapore Sound” in Saxophone Compositions of Zechariah Goh - Ho, Leslie Wong Kah; Bampenyou, Rattanai (Harmonia: Journal of Arts Research and Education, 2023)
The main objective of this study is to examine two of Goh’s saxophone works that demonstrate how the composer realized Singaporean identity through the synthesis of Western, Tibetan, and Indian musical elements. The research design of this qualitative case study is narrative research with data collection carried out by semi-structured questions, email interview with the composer and review of text, videos, and journal articles that relate to the government policies of racial integration and multiculturalism in Singapore, followed by analysis of two of the recent works that evolved from the fusion of Eastern and Western styles. The two works for this qualitative study are Images of Tibet for Soprano Saxophone and Piano, and Confluence for Saxophone Ensemble and Mridangam. The findings show that 1) Images of Tibet uses Western formal structures, the technique of thematic development, and Tibetan musical idioms; and 2) Confluence for Saxophone Ensemble and Mridangam employs the Indian Tala, motivic modification technique used in the Fugues of Johann Sebastian Bach, and pandiatonicism as employed in Impressionistic works of Debussy and Ravel. This study reveals the two ways in which the composer uses to intertwine the East and West in his connection to his cultural roots.